Testing large area lysimeter designs to measure leaching under multiple urine patches. Issue 2 (3rd April 2017) - Carrick, Sam; Rogers, Graeme; Cameron, Keith; Malcolm, Brendon; Payne, John
ABSTRACT: A novel, large area, repacked rectangular shipping container lysimeter (13.8 m 2 ) was compared with those from undisturbed monolith barrel lysimeters (c. 3.1 m 2 ), to evaluate their utility for measuring leaching under soil with multiple urine patch depositions. In July 2015, the rectangular and three barrel lysimeters had 31 and 7 patches, respectively, of synthetic cow urine applied at 3.24 g N L −1, covering 52% of the lysimeter surface area. The lysimeters then remained fallow while receiving rainfall and irrigation. Drainage and leaching dynamics were monitored until June 2016. Results indicate that the large area barrel lysimeters showed consistent dynamics in drainage, as well as bromide and nitrogen leaching. The rectangular lysimeter differed in drainage and nitrate leaching patterns compared to the barrel lysimeters. This was interpreted as reflecting changes in the pore size distribution and pore continuity that was created during the repacking of the rectangular lysimeter.